Gluten-free diet among school-age children in Olmsted County, Minnesota - Eyad Almallouhi (Thieme Medical and Scientific Publishers Pvt. Ltd., 2017)
Objective: To assess the prevalence of gluten-free diet (GFD) among school-age children in Olmsted County, Minnesota, and compare it with the prevalence of celiac disease (CD) in the same age group. Methods: We performed a population-based study in Olmsted County using a survey to collect information from the six school districts in the county for the academic year 2014–2015. The survey contained questions to (1) assess the prevalence of GFD among school-age children in the public schools of Olmsted County; (2) assess the prevalence of CD among school-age children in Olmsted County; and (3) determine the indications for GFD in these children. We used the infrastructure of the Rochester Epidemiology Project (REP) to calculate the prevalence of CD in children aged 4–18 years in December 2014. Results: Using the REP data, we identified sixty patients with CD in the county aged 4–18 years; the prevalence of CD among school students in 2014 was 193.6/100,000. The prevalence of GFD in Olmsted County children, however, was higher, at 265/100,000 according to the survey from the school districts. The prevalence of GFD was highest in Rochester, the largest city. GFD was more common among children in secondary schools. Conclusion: According to our study, there are more children on GFD than the actual cases of CD in Olmsted County during the study period. This finding could be related to an increased number of children without CD who are following GFD for other indications.